Adolescent acne vulgaris: current and emerging treatments. (February 2023) - Layton, Alison M; Ravenscroft, Jane
Summary: Acne vulgaris is one of the commonest inflammatory skin diseases seen worldwide, affecting all ethnicities and races, with a peak prevalence between age 15 years and 20 years. The burden of this condition, and the resulting clinical and psychological sequelae, is substantial. The visual appearance of acne and its sequelae, including scarring and pigment changes, frequently results in psychological and social morbidity because of concerns about appearance. As understanding of the pathophysiology has evolved, approaches to achieving the optimal outcomes with effective treatment regimens continue to emerge. In the past few years, several novel therapeutics have been developed, including new agents aimed at reducing antimicrobial resistance and products with specific actions targeting retinoid receptors and androgen receptors. This Review considers the management approaches of an adolescent with acne vulgaris and reviews treatment options from the evidence base and international expert opinion. Approaches to selecting current treatments and novel and emerging treatment regimens are discussed.